Determinants of unfair labour practices on African migrant labourers employed in selected labour sectors in South Africa - Mafa, Prudence; Makhubele, Jabulani (Technium Social Sciences Journal, 2021)
Migration for the purpose of improving one’s economic status is one of the major reasons for human mobility. Over the years South Africa has been the biggest host of migrants in the continent. The objective of this study was to describe factors that predispose migrant workers to unfair labour practices. African-born migrant workers were conveniently selected to participate in this descriptive qualitative study through the use of a focus group and individual interviews. The findings show that migrants experience exploitation in their workplaces on account that they enter the country illegally, they are desperate to find a source of income, they are afraid to speak out about the labour injustices that they experience, and there exists a corrupt relationship between authorities and employers. Employers need to abide by labour regulations that are relevant to their sector. There is also a need to protect the rights of migrant workers, irrespective of their status in the country.